“If You Fall Down, You Get Back Up”: Creating a Space for Testimony and Witnessing by Urban Indigenous Women and Girls - Cooper, Elizabeth; Driedger, S Michelle (International Indigenous Policy Journal, 2019)
Historical trauma and the negative effects of colonialism continue to be played out within Canadian culture. These processes have a deleterious effect on physical and psychological health outcomes among Indigenous Peoples. Through the creation of a safe space as part of a decolonizing, participatory activity program spanning 7 weeks, First Nations and Metis women and girls (aged 8-12) were able to begin to unpack what it means to be happy, healthy, and safe, and what is needed to actualize these goals. A community engaged, asset-based workshop approach provided a forum for participants to discuss the impact of traumatic experiences on the ability of adults to model a positive image of strength, independence, and confidence for their daughters, while creating a space to discuss change.